Characterization and Anti-Corrosion Study on Different Substituents of Ni(Ii) Dithiocarbamate Complexes - R. Mohd Zambri, S.; S. Habdul Latif, N.; N. Mohd Zulkamal Punnia, N.; A. I. Sheikh Mohd Ghazali, S.; N. Dzulkifli, N. (International Journal of Engineering and Technology, 2018)
Dithiocarbamate is a ligand that can act as a corrosion inhibitor due to the presence of sulphur and nitrogen atoms. Ni(II) N-methylcyclohexyl dithiocarbamate, Ni[MeCycHexdtc]2 and Ni(II) N-ethylcyclohexyldithiocarbamate, Ni[EtCycHexdtc]2 complexes were synthesized through direct synthetic method at room temperature and characterized using the Elemental Analyzer (CHNS), Fourier Transform Infrared-Attenuated Total Reflectance (FTIR-ATR), Ultraviolet-Visible (UV-Vis), Nuclear Magnetic Resonance (NMR), molar conductivity, and gravimetric analysis. The Ni[MeCycHexdtc]2 complex had indicated a square planar geometry, but it was not the case for the Ni[EtCycHexdtc]2 complex which showed a tetrahedral geometry. The efficiency of the synthesized inhibitors was studied in different concentrations; 0.001 M, 0.01 M, and 0.1 M (1 M HCl and 1 M H2SO4) at room temperature.Â Â